2018
DOI: 10.1002/bse.2051
|View full text |Cite
|
Sign up to set email alerts
|

With a little help from a stranger: The impact of external change agents on corporate sustainability investments

Abstract: We investigate the role external change agents (e.g., consultants), play in stimulating corporate sustainability investments. Using data on more than 5,300 energy efficiency investment decisions by 462 firms, we find that firms that draw more strongly on external change agents seize significantly more sustainable investment opportunities. We show that external change agents are more effective in stimulating investments if they broadly search for investment opportunities and are more strongly involved in the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…Meanwhile, a firm with various internal cognitive pressures may produce a biased estimation on external institution‐level pressures in accordance with fit or misfit demands. This estimation may influence the firm's resource and attention reallocation to converge on or deviate from the specific cognitive process (Fini & Toschi, ; Hoppmann, Sakhel, & Richert, ; Lee & Zhou, ). In this view, we propose a research model, as shown in Figure .…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Meanwhile, a firm with various internal cognitive pressures may produce a biased estimation on external institution‐level pressures in accordance with fit or misfit demands. This estimation may influence the firm's resource and attention reallocation to converge on or deviate from the specific cognitive process (Fini & Toschi, ; Hoppmann, Sakhel, & Richert, ; Lee & Zhou, ). In this view, we propose a research model, as shown in Figure .…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Individuals who initiate, promote, or implement change toward sustainable development are usually called sustainability change agents (Davis & Boulet, ; Heiskanen, Thidell, & Rodhe, ; van Poeck, Læssøe, & Block, ; Weerts et al, ) and sustainability, environmental, or “social” champions (Andersson & Bateman, ; Corbett et al, ; Visser & Crane, ). They can come from various levels of the company or from outside of the company, such as project employees, CSR managers, or external consultants (Carollo & Guerci, ; Corbett et al, ; Hoppmann, Sakhel, & Richert, ; Lozano, ). Change agents perform various tasks; for example, they use their influence on internal networks to generate and diffuse cross‐departmental knowledge (Siebenhüner & Arnold, , p. 344), identify environmental issues or generate ideas, package, that is, frame and present them, attractively, and sell them to organizational decision‐makers (Andersson & Bateman, , p. 549).…”
Section: Theoretical Background and Conceptual Frameworkmentioning
confidence: 99%
“…The results of the overall hypothesis test are presented in Table 2 as follows. Y1= 0,600 X1 + 1 R 2 = 0,360 (1) Y2 = 0,671Y1 + 2 R 2 = 0,450 (2) Y3= 0,457 Y1+ 0,507Y2+ 3 R 2 = 0,777 (2)…”
Section: Analitycal Resultsmentioning
confidence: 99%